MEASURING THE DOMESTIC AND FOREIGN TOURISTS SATISFACTION TOWARDS THE TOURISM MARKETING MIX IN THE EQUATOR CITY: MEASURING THE DOMESTIC AND FOREIGN TOURISTS SATISFACTION TOWARDS THE TOURISM MARKETING MIX IN THE EQUATOR CITY - Barkah; Erna Listiana; Wenny Pebrianti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2020)
Abstract: West Kalimantan is one of the Indonesias provinces with strategic location because it is adjacent with neighboring country (Malaysia). The location within the border area and crossed by equator line is expected in impacting the tourism industry. This research aims to examine and to analyse the influence of tourism marketing mix towards the domestic and foreign tourists satisfaction. Population in this research is the tourists visiting Pontianak.. Sampling method was done by using purposive sampling with total amount of 242 people. Data collection by distributing questionnaires and analyzed using Multiple Linear Regression. The result shows that there are different variables influence both domestic and foreign tourists satisfaction. For the domestic tourists; product, price, promotion, and physical evidence impact their satisfaction. However for the foreign tourist, only variable of promotion and people, while the other five variables is not significantly impacted. Keywords: tourism marketing mix, tourists satisfaction, equator city